Finance Risks and Sources of Financing Sustainable Development: Global and Russian Aspects - I. P. Khominich; Nguyen Huu Duc (Вестник Российского экономического университета имени Г. В. Плеханова)
In times of sharp aggravation of the sanction war against the Russian Federation, global power crisis and highest geo-political and geo-financial risks the world community, including the Russian Federation, keeps on moving towards carbon neutrality. It takes place in spite of dropping global investment caused by the pandemic and sanctions, reduction in carbon deals and turbulent finance and power markets. On this way within the frames of the green agenda serious risks such as deficit of sustainable development financing, low share of undeveloped countries and prevalence of state funds in financing were encountered. The article estimates investment needs of the global program of sustainable development by industries, where the highest share falls to power engineering. It identifies sources of investment: private capital of institutional investors, international finance organizations, international banks of development and state funds. And finally, it provides expert opinions of the IMF concerning the volume of deficit in financing and problems of undeveloped countries, which due to limited national finance markets cannot use market financial tools of investment raising for projects of green technologies. The authors focused on the most capital-intensive industry of the green agenda, i.e. power and on energy-transition to carbon neutrality. They pointed out to finance risks of energy-transition and such urgent problems, as searching for sources of financing, for investors that are ready to put capital into risky low-carbon projects with a long pay-back period, building new finance schemes of participant interaction, developing innovative finance products.